The Effect of Interpersonal Skills on Performance of Regional Secretariat Employees in Kapuas Hulu Regency - Husni Syahrudin (STKIP Singkawang, 2018)
The facts that occur in the field show that the performance of government employees as public services still has not achieved the performance increased; based on the Government Agency Performance Accountability Report of the Kapuas Hulu Regency regional secretariat in 2012. The purpose of this study was to determine the Effect of Interpersonal Skills on the Performance of the Kapuas Hulu Regency Regional Secretariat Staff. This study uses a quantitative research approach the method used is the survey method. The population in this study were all employees (civil servant status) who worked in the regional secretariat of Kapuas Hulu Regency, totaling 137 employees. The sampling technique uses Simple Random Sampling. Based on the results of sample calculations in this study there were 102 employees. The research instrument used was a questionnaire. Data analysis in this study was conducted using descriptive statistical analysis techniques and statistical inferential. Based on the results of testing the hypothesis it can be concluded that Interpersonal Skills have a positive direct effect on employee performance. That is, improving employee performance at the Kapuas Hulu Regency Regional Secretariat can be done by increasing the interpersonal skills possessed by employees.